Вярхоўя Пцічы у Х—ХІ стст. (па матэрыялах даследаванняў курганных могільнікаў) - Вайцяховіч, А.В. (Археологія і давня історія України, 2021)
Анатацыя: артыкул прысвечаны вывучэнню курганных старажытнасцей звязаных з ракой Пціч і
размешчаных на тэрыторыі Мінскага раёна ў Беларусі. The Ptich river, a left tributary of the Pripyat, flows
through the southern part of Central Belarus. Its banks
are mostly swampy. The most suitable land for farming
is located in the upper parts of the river, on the territory
of Minsk district. The location of 60 burial mounds
specifically connected with this region (fig. 1), but unfortunately
most of them had not been preserved. Only
five sites were investigated by archaeological excavations.
Six burial mounds with cremation were explored
in the burial ground of Ozerzo which dated back to the
the second half of the 10th century (fig. 2—5). Wooden
constructions of log walls and boxes were fixed in some
mounds, which might be compared with the traditions
of the Slavs of the Raikovetskaya and Romny-Borshevo
Cultures. The grave goods are presented by artefacts
connected with subculture of armed force centers and
prestigious women’s jewelry (fig. 6—8). The burial
ground of Ozertso could be the part of a large one and
now this necropolis was completely destroyed. It can
only be assumed that the site was an integral part of
the settlement on the Menka river, which was the original
location of Minsk. Some prestigious women’s jewelry
made of silver was also found in the plowed area
nearby (fig. 9). Such places as Gorodishche, Dudovka,
Priluki related to the burial grounds of the nearest
district of the settlement on the Menka river present
cremations of the late 10th century and inhumations of
the 11th century (fig. 13, 14). Axes were found in men’s
burials, and ornaments typical of the Dregovichy were
discovered in women’s ones, pottery was found both
ways (fig. 10, 11, 15—18). The studied burial ground of
Dovborovo up the Ptich river provides cremations and
inhumations and grave goods which dated back to the
late 10th — the first half of the 11th century and display
typical rural items (fig. 12).
Thus, by the late 10th century, the entire territory
of the upper reaches of the Ptitch river was inhabited.
The trade and craft settlement was founded on
the banks of the Menka river, the right tributary of
the Ptitch, which in the early 11th century turned into
a well-fortified pre-urban place. Burials in the necropolis
of this settlement are distinguished by a variety
of ritual elements and prestigious grave goods.
A new fortified place of Minsk was built on the Svisloch
river in the second half of the 11th century, which
later became the center of the Principality. The intensity
of life in the region of the upper Ptitch river
was gradually decreasing by the 12th century, and numerous
rural settlements were connected to the new center. Річка Птич, ліва притока Прип’яті, протікає в
південній частині Центральної Білорусі. Її береги,
головним чином заболочені. Найбільш придатні до
землеробства землі розташовані в верхів’ях річки,
на території Менського району. Відомо місце розташування 60 курганних могильників, безпосередньо
пов’язаних з басейном верхів’я Птичі (рис. 1), проте
більша частина з них не збереглась. Археологічні
дослідження проводились на 5 могильниках. В моми кремацій другої половини Х ст. (рис. 2—5). У деяких курганах знайдені дерев’яні конструкції: зруби
та ящики, які відповідають традиціям слов’янських
культур: боршевської та лука-райковецької. Інвентар представлений речами, пов’язаними з дружинною субкультурою та престижними жіночими прикрасами (рис. 6—8). Могильник Озерцо є частиною
більшого, зараз уже розораного некрополю поселення на р. Менка, яке було початковим місцем розташування м. Мінська. В розораній частині могильника також були знайдені престижні жіночі прикраси,
виготовлені зі срібла (рис. 9). В могильниках найближчої округи поселення на р. Менка (Городище,
Дудовка, Прилуки) знайдені кремації кінця Х ст. та
інгумації ХІ ст. (рис. 13, 14). В похованнях чоловіків
знайдені сокири, в похованнях жінок прикраси, характерні для дреговичів. В похованнях обох статей
були зафіксовані горщики (рис. 10, 11, 15—18). В
самому верхів’ї річки досліджено могильник Довборово, де також було виявлено кремації та інгумації
кінця Х — першої половини ХІ ст., інвентар характерний для сільських могильників давньоруського
часу.
Таким чином, до кінця Х ст. всі території верхів’їв
Птичі були заселені. На річці Менка, правій притоці
р. Птичі було засновано торгівельно-ремісниче поселення, яке на початку ХІ ст. перетворилось у добре
укріплене протомісто, центр волості. Поховання на
некрополі цього поселення відрізняються різноманіттям елементів обряду та престижним реманентом. У
другій половині ХІ ст. на Свіслочі зведено нове укріплене місто Мінськ, який незабаром стає центром
княжіння. До ХІІ ст. інтенсивність життя в регіоні
верхів’їв Птичі поступово зменшувалось, а чисельні
сільські поселення почали тяготіти до нового центру.